Salaborsa library in Bologna: semiotic analysis of a sound space - De Bortoli, Luca (E|C, 2020)
This paper aims to provide a semiotic analysis of Salaborsa – the main public library in Bologna – through the study of two sensory dimensions (spatial and acoustic) and their correlation. By applying tools of the semiotics of space (such as the recognition of thresholds and borders) it has been possible to establish the composite nature of Salaborsa: it presents itself as a complex space composed of different autonomous spaces, each one having its own specific functions, not always and not only inherent to those of a library. A second research direction (the acoustic one), through on-site and in-motion recordings in different moments, allowed for the construction of an acoustic trace, which presents a clear segmentation in acoustic syntagms, replicating the same earlier established segmentation in partial spaces, and highlighting their interdependence. Studying a syncretic text such as a space calls for the adoption of an integrated approach, that could correlate several sensory dimensions as distinct expressions of the same content and modalizations. In the case of Salaborsa, the same structure, conveying the same contents, is pinpointed by the analysis of the two dimensions. Lastly, it evokes a structural and internal coherence of the whole, allowing for an optimal use by the subjects.